The Analysis Study of Association of Myopia and Age-Related Cataract: A Comprehensive Systematic Review - Fazri, Karin Ananditya; Ramadhani, Fikar (The International Journal of Medical Science and Health Research, 2024)
Background: Cataract is a major burden for health-care providers around the world. From a public health perspective, it is important to know the prevalence of undiagnosed lens opacities. Myopia a refractive error where distant objects appear blurred due to the elongation of the eyeball is seeing a rise in prevalence worldwide, with a particular increase in Asian populations. The aim: The aim of this study to show about association of myopia and age-related cataract. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Low and moderate myopes are less likely to develop such a severe visual outcome; nevertheless, they are at significant risk to develop cataract.